SELF-HELP GROUPS – AN INSTRUMENT FOR THE DEVELOPMENT OF RURAL WOMEN ENTREPRENEURSHIP - Vijayamalleeswari, K.R.; Mugunthan, C. (International Journal of Psychosocial Rehabilitation, 2020)
Women play a significant role for the development of family, community, region and country. According to their interest, areas of Self-Help Group are to put together women socially and economically strong and skilled. For the poor and marginalized women, Self-Help Group is generating earnings and employment opportunities. Self-Help Group helps the members for empowering the rural poor women and generating employment for them. In this study, the primary data were collected from different Self-Help Groups with a sample size of 200. The questionnaire is used for the data collection. For becoming an entrepreneur, the study showed that knowledge, skill, attitude and training programmes are need of hour and Self-Help Group members were economically empowered and motivated.